PERENCANAAN KEHIDUPAN BERKELUARGA OLEH REMAJA SMA DI KABUPATEN MALANG - Kusumo Projo, Nucke Widowati; Natalia, Christiayu (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
Teenagers are one of investments of the country and they should prepare their capacity buildings include family life planning. However, there are indications of family life planning behavior is not good as it occurs in adolescents in Malang. This study aims to determine the effect of the variables of knowledge and attitude towards family life planning behavior in tenth and eleventh grade of Senior High School / equivalent in District Tumpang Malang. This research used stratified cluster sampling as sampling method. The analytical methods for this research are descriptive analysis and Structural Equation Modeling (SEM). The results as follow: (1) variables of knowledge and attitude affectsdirectlyto the adolescent’s behavior of family life planning. (2) Knowledge also indirectly affects the behavior of family life planning through attitude. Therefore, the Family Planning Board (BKB) and Malang Regency High School / equivalent in District Overlapping should work together to improve students' knowledge of family life planning behavior through a more effective counseling.